Multifunctional heterogeneous ion-exchange membranes for ion and microbe removal in low-salinity water - Mudau, Fulufhelo H.; Hassard, Francis; Motsa, Machawe M.; De Kock, Lueta-Ann (MDPI, 2023)
Here, multifunctional heterogeneous ion-exchange metal nanocomposite membranes were prepared for surface water desalination and bacterial inactivation under low-pressure (0.05 MPa) filtration conditions. Ultrafiltration (UF) heterogeneous ion exchange membranes (IEMs) were modified with different concentrations of AgNO3 and CuSO4 solutions using the intermatrix synthesis (IMS) technique to produce metal nanocomposite membranes. Scanning electron microscopy (SEM) images revealed that the metal nanoparticles (MNPs) (Ag and Cu) were uniformly distributed on the surface and the interior of the nanocomposite membranes. With increasing metal precursor solution concentration (0.01 to 0.05 mol·L−1), the metal content of Ag and Cu nanocomposite membranes increased from 0.020 to 0.084 mg·cm−2 and from 0.031 to 0.218 m·cm−2 respectively. Results showed that the hydrodynamic diameter diameters of Ag and Cu nanoparticles (NPs) increased from 62.42 to 121.10 nm and from 54.2 to 125.7 nm respectively, as the metal precursor concentration loaded increased. The leaching of metals from metal nanocomposite membranes was measured in a dead-end filtration system, and the highest leaching concentration levels were 8.72 ppb and 5.32 ppb for Ag and Cu, respectively. The salt rejection studies indicated that ionic selectivity was improved with increasing metal content. Bacterial filtration showed higher antibacterial activity for metal nanocomposite membranes, reaching 3.6 log bacterial inactivation.
Keywords: heterogenous ion exchange membranes; ultrafiltration; silver nanoparticles; copper nanoparticles; intermatix synthesis; surface water treatment; Escherichia coli inactivation